A abertura dos portos do Brasil em 1808: dos factos à doutrina - José Luís Cardoso (Ler História, 2008)
The first decree of Regent Prince D. João when he arrived in Bahia, in January 1808, was the opening of Brazilian ports to trade with friendly nations. For this decision making, and to the justification of its legitimacy and importance, José da Silva Lisboa played a relevant role. This event offers unmistakable evidence of deep changes in the usual forms of dealing and thinking the economic relationship between the metropolis and the main colony. Therefore, that is why the explanation of the doctrinal principles and practical implications of this process is still of decisive importance for the comprehension of the dilemmas along the Portuguese Court stay in Brazil.